Examining barriers and facilitators of graduate international students in the U.S. - Bayati, Niloufar; Denson, Cameron; Asunda , Paul (Journal of International Students, 2025)
As international student enrollments surge in U.S. higher education, understanding their experiences is crucial for fostering an inclusive and successful environment. This study used a hermeneutic phenomenological approach to explore the challenges and coping strategies of international students during acculturation. Data were collected through in-depth interviews with eight international graduate students from diverse backgrounds at a large U.S. public research-based university. An inductive, hermeneutic approach revealed six main challenges: 1) cultural differences and adjustment, 2) practical and daily living, 3) academic and educational, 4) mental health and well-being, 5) linguistics and communication barriers, and 6) lack of resources. Students reported resilience strategies and four main coping mechanisms and needs for better adjustment: 1) building connections and social support, 2) cultivating resilience and personal development, and 3) leveraging technology and media. The findings of this research highlight the importance of social support and self-resilience for international students.